Mortalités massives de l'huître creuse - Rapport final du programme de recherche sur l'étude de la cinétique de détection d'agents infectieux associés à des épisodes de mortalités de naissains d'huîtres creuses Crassostrea gigas sur un site ostréicole de Marennes-Oléron (CIDAGINF 2009-2010) - Saulnier, Denis; Pepin, Jean-francois; Guesdon, Stephane; Degremont, Lionel; Faury, Nicole; Haffner, Philippe; Renault, Tristan; Travers, Marie-agnes; Tourbiez, Delphine; Geairon, Philippe; Le Moine, Olivier; Seugnet, Jean-luc; et al. (2011)
This study aims to improve understanding of causes of mortalities in oyster Crassostrea gigas in pertuis charentais related to environmental parameters and the kinetics of targeted infectious agents, such as bacteria Vibrio splendidus (group ) and V. aestuarianus and Ostreid herpesvirus OsHV-1. Two sampling campaigns were carried out on the site of Agnas in 2009 and 2010, before, during or following mortality events of spat from March to September. The approach is to detect and quantify in short time step infectious agents from tissues of farmed oysters placed on rack and in various samples taken nearby: native oysters and other species (wild mussels and barnacles), seawater and sediment. With physical and chemical automatic probes placed on the site, environmental parameters kinetics have been achieved (temperature, salinity, turbidity, fluorescence eq. Chlorophyll, Oxygen). Data from these parameters have allowed to note that the periods of mortality are preceded by a rise in temperature of the water column (+0.5°C/day, > 4 days). Oyster mortalities were observed six days after the temperature peak, with water above 16°C. Kinetic of bacteria belonging to the Vibrio splendidus group shows that they are frequently detected in the living spat sampled before or during periods of mortality. The levels of bacterial loads detected in the tissues do not increase or slightly during periods of increased mortality. The kinetic of OsHV-1 viral DNA detection shows that the virus is poorly or not detected except mortality event, while its prevalence is increasing rapidly just before and during mortality outbreaks. The levels of viral loads detected in tissues rise sharply during mortality events. The infectious nature of observed mortalities is well established, however, the bacterium V. aestuarianus was not detected. This study for the first time has allowed to demonstrate OsHV-1 viral DNA in mussels and barnacles, but also in seawater out or during mortality events. The temperature factor appears to play a key role in ...